Implementation of STEAM and Thematic Learning Models Assisted by STEMATIK Learning Media in Elementary School - Hazima, Atika Azzahro; Prasetyo, Eko; Annisa, Aulia Hanif; Maryanti, Ranti (Mathematics Education Journal, 2024)
Learning is not only about giving theories, but instilling concepts is more important to teach to students. One of the concepts instilled in mathematics, namely the arithmetic material of addition and subtraction for elementary school. STEMATIK learning media supports students' understanding in introducing the arithmetic concepts of addition and subtraction for lower elementary school classes. This research aimed to explain the component analysis of integrating STEAM and thematic learning using STEMATIK learning media, to describe the importance of using learning media in enhancing students’ independence and motivation to learn, and to present the results of using STEMATIK learning media as a tool for learning mathematics.  The research method employed was a quasi-experiment. Quantitative data analysis was conducted to analyze the data collected from the research instrument, including validation instruments by two experts in the form of learning media feasibility instruments and pretest and posttest assessment results on 31 elementary school students on the control group and the experimental group. The validity test used T-test by SPSS application. The product development process was based on the ADDIE model, a systematic approach that includes five stages: analysis, design, development, implementation, and evaluation. The method used in this research was the descriptive, qualitative and quantitative method. The research results show that for the validity test the increase in knowledge scores significantly using the T test with the SPSS application produces two sides of less than 0.001. The level of student learning independence is good, achieving a score of 68,14, which according to the category is considered good. The percentage for the student learning motivation category falls into the high criterion. The result of these indicators shows a score of 83, which is categorized as high.